Climate change and maize productivity in Uganda: Simulating the impacts and alleviation with climate smart agriculture practices. (May 2022) - Zizinga, Alex; Mwanjalolo, Jackson-Gilbert Majaliwa; Tietjen, Britta; Bedadi, Bobe; Pathak, Himanshu; Gabiri, Geofrey; Beesigamukama, Dennis
Abstract: CONTEXT: Climate change continues to affect maize production, food security and livelihoods of smallholder farmers in most of the developing countries. Climate smart agriculture (CSA) practices can enhance agricultural production by alleviating adverse climate effects on maize productivity through improved soil moisture storage, water use efficiency, increased soil carbon (C) and nutrient supply with long-term resilience to climate change. OBJECTIVE: This study investigated the effectiveness of CSA practices (mulching at 0, 2, 4 and 6 cm thicknesses), permanent planting basins (20 and 30 cm deep), and halfmoon pits as a mitigation and adaptation strategy for improving maize productivity in rainfed production systems in the sub-humid regions of Sub-Saharan Africa. METHODS: We used the AquaCrop model of the Food and Agriculture Organization (FAO, 2018), AquaCrop version 6.1 to evaluate potential benefits of the CSA practices: half-moon, mulching (using different thickness) and permanent planting basins compared to a control treatment in rainfed production systems. The performance of CSA practices was evaluated using field experiments under present and future conditions. We first parameterized the model based on a three-season field experiment (2019-2020). We then run the model under projected future trends (2010–2039) using four general circulation models in each two greenhouse gas (GHG) emission representation concentration pathways (RCP4.5 and RCP8.5) for the Coupled Model Inter-comparison Project 5 (CMIP5). Finally, we evaluated resulting maize growth, grain yield, and water use efficiency for all the treatments. RESULTS AND CONCLUSIONS: Our results indicated that use of mulching, especially 6 cm thick mulch increased maize grain yield and water use efficiency under present and future conditions. It was noted that CSA practices would increase grain yield by 14–37% under RCP8.5 climate scenario. Projections revealed increases in mean temperature of 0.5 °C and 1.0 °C under RCP4.5 and RCP8.5, respectively, in the 30 years (2010–2039). The model also projected a decrease (4.7%) and increase (2%) of the annual averages of rainfall in the future under RCP4.5 and RCP8.5, respectively. SIGNIFICANCE: Our findings highlight the key role of CSA practices in reducing the climate change effects on maize production in the sub-humid regions. Therefore, national governments should prioritize adoption of climate smart agriculture practices as a key strategy for improving and sustaining maize productivity in rainfed systems of the sub-humid region. Graphical abstract: Unlabelled Image Highlights: In Uganda, temperatures are projected to increase by 0.5-1.0 ºC while rainfall will decrease from 2010-2039. The impacts of climate smart agriculture (CSA) on maize productivity under changing climate were evaluated and projected. AquaCrop model projections indicate that CSA will increase maize grain yield by 14-37% in rainfed production systems. Mulching and permanent planting basins were the most effective for improved maize yield and water use efficiency.